2018
DOI: 10.3899/jrheum.171094
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Axial Involvement on Clinical Characteristics of Psoriatic Arthritis: Analysis from the Corrona Psoriatic Arthritis/Spondyloarthritis Registry

Abstract: Presence of axial involvement was associated with a higher likelihood of moderate/severe psoriasis, with higher disease activity and greater effect on quality of life. These findings highlight the importance of monitoring patients with PsA for signs of axial symptoms or spinal involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
63
1
47

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 108 publications
(111 citation statements)
references
References 38 publications
0
63
1
47
Order By: Relevance
“…Furthermore, PsA is a systemic disease that affects many joints, including axial joints. A previous study showed that the presence of axial involvement was associated with higher disease activity, including CRP and VAS 29 . Hence, results of the blood samples may not completely reflect the state of joints in the hand and foot.…”
Section: Inter-reader Reliabilitymentioning
confidence: 91%
“…Furthermore, PsA is a systemic disease that affects many joints, including axial joints. A previous study showed that the presence of axial involvement was associated with higher disease activity, including CRP and VAS 29 . Hence, results of the blood samples may not completely reflect the state of joints in the hand and foot.…”
Section: Inter-reader Reliabilitymentioning
confidence: 91%
“…In treating PsA patients, we should consider the considerable percentage of PsA patients having axial involvement and choose the right biologic agent. Mease et al found the clinical characteristics of 192 PsA patients with axial involvement by comparing them with 1338 PsA patients without it [48]. Axial involvement was defined as physician-reported presence of spinal involvement at enrollment, and/or radiograph or MRI showing sacroiliitis.…”
Section: Psoriatic Arthritismentioning
confidence: 99%
“…Между тем своевременная диагностика спондилита крайне важна, поскольку поражение позвоночника рассматривается как фактор неблагоприятного прогноза ПсА, который существенно влияет на выбор лечения, в том числе ГИБП. По данным ряда крупных наблюдательных исследований, спондилит чаще выявляется у носителей HLA-B27-антигена и ассоциируется с развитием эрозивного артрита, энтезита и более тяжелого псориаза ногтей по индексу NAPSI (Nail Psoriasis Severity Index [23,24]. Однако авторы этих работ отмечают, что позитивность по HLA-B27-антигену не может быть облигатным признаком развития спондилита при ПсА, так как частота его при этом заболевании составляет 40-50%.…”
Section: клинические проявления псаunclassified